Navigating the climate-finance landscape in Eastern Africa: An exploration of climate and agriculture finance instruments - Chilambe, Pedro; Nguvi, Caroline; Zulu, Mercy; Jalango, Dorcas; Mundia, Carolyne (2024)
A massive level of sustained investment is needed to help developing countries in Africa meet the goals set forth in their Nationally Determined Contribution (NDC) submitted to the United Nations Framework Convention on Climate Change (UNFCCC). The annual financing gap between resources available and resources needed is $200-$400 billion, and this deficit is expected to grow unless funds from new sources are identified and allocated1. The purpose of this research report is to explore climate and agriculture finance instruments available in Uganda, Kenya, Ethiopia, and South Sudan, and identify which institutions (mainly government agencies, banks, and corporations) are providing these climate-finance solutions. This report also explores programs available through international multilateral climate funds and multilateral development banks, and the potential for increased participation in carbon pricing markets, such as the Clean Development Mechanism (CDM).